Anchorage of γ-Al2O3 nanoparticles on nitrogen-doped multiwalled carbon nanotubes. (October 2016) - Rodríguez-Pulido, A.; Martínez-Gutiérrez, H.; Calderon-Polania, G.A.; Lozano, M.A. Gonzalez; Cullen, D.A.; Terrones, H.; Smith, D.J.; Terrones, M.
Abstract: Nitrogen-doped multiwalled carbon nanotubes (CNx-MWNTs) have been decorated with γ-Al2 O3 nanoparticles by a novel method. This process involved a wet chemical approach in conjunction with thermal treatment. During the particle anchoring process, individual CNx-MWNT nanotubes agglomerated into bundles, resulting in arrays of aligned CNx-MWNT coated with γ-Al2 O3 . Extensive characterization of the resulting γ-Al2 O3 /CNx-MWNT bundles was performed using a range of electron microscopy imaging and microanalytical techniques. A possible mechanism explaining the nanobundle alignment is described, and possible applications of these materials for the fabrication of ceramic composites using CNx-MWNTs are briefly discussed. Graphical abstract: